2015
DOI: 10.1007/s10853-015-9131-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of sigma-phase evolution in thermally aged 2205 duplex stainless steel

Abstract: In this study, the evolution of sigma-phase development in a 2205 duplex steel was studied following thermal ageing in the temperature range 750-850°C for periods up to 100 h. A suite of materials analysis techniques including combined electron backscatter diffraction-energy-dispersive X-ray imaging and magnetic force microscopy are used to quantify the change in volume fraction of the phases. The experimental results for each ageing condition are compared with the results from other ageing experiments and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…Ferrite and austenite also did not show any specific texturing before aging, as shown in Figure 3. A similar observation was reported by Warren et al [35], who concluded that no specific σ nucleation orientation relationship relative to the parent δ was favored. However, it is not possible to conclude whether the apparently random orientation of σ was inherited from the parent δ or not.…”
Section: Discussionsupporting
confidence: 87%
“…Ferrite and austenite also did not show any specific texturing before aging, as shown in Figure 3. A similar observation was reported by Warren et al [35], who concluded that no specific σ nucleation orientation relationship relative to the parent δ was favored. However, it is not possible to conclude whether the apparently random orientation of σ was inherited from the parent δ or not.…”
Section: Discussionsupporting
confidence: 87%
“…It has been proved that pitting occurring in chromium-depleted areas are associated with the precipitated phase [30,31]. When combined with Figures 2f and 7a, the ferrite was almost occupied by the σ phase and the secondary austenite, which often has relatively low Cr content than the σ or…”
Section: Discussionmentioning
confidence: 84%
“…No sigma phase appears below 650˚C. The longer stayed at 850˚C, the more of the σ phase precipitation [5] [6].…”
Section: N Content σ Phase Control Cooling Rate Considerationmentioning
confidence: 99%